On the Effects of Sanctions on Trade and Welfare: New Evidence Based on Structural Gravity and a New Database - Gabriel J. Felbermayr; Constantinos Syropoulos; Erdal Yalcin; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2019)
Using a new, global data base covering the years 1950 to 2015, we study the impact of sanctions on international trade and welfare. We make use of the rich dimensionality of our data and of the latest developments in the structural gravity literature. Starting with a broad evaluation by sanction type, we carefully investigate the case of Iran. Effects are significant but also widely heterogeneous across sanctioning countries. Moreover, they depend on the direction of trade. We also perform a counterfactual analysis which translates our partial equilibrium sanction estimates into heterogeneous but intuitive general equilibrium effects within the same framework.
Keywords: F10; F13; F14; F50; F51; H50; N40; 330; sanctions; effectiveness of sanctions; structural gravity